Designing the curriculum - Sockett, Hugh (Open Books Publishing, 1976)
This text examines the curriculum using a wide lens, accounting for both macrocurricular and microcurricular levels, making distinctions between instruction and pedagogy (as well as between evaluation and assessment) and demonstrates to the reader how to coordinate a curriculum design that meets the needs of each school.